Artificial intelligence for training and reporting infection prevention measures in critical wards - Simioli, Francesca; Annunziata, Anna; Coppola, Antonietta; Iervolino, Anna; Boccia, Mariacristina; Fiorentino, Giuseppe (Frontiers in Public Health, 2024)
Healthcare associated infections (HAI) are a major concern. Infections and sepsis are prevalent causes of prolonged hospitalization, healthcare resources consumption, and mortality. Infection prevention and control (IPC) measures need to be encouraged with the purpose to become standard protocol. Hand hygiene represents the most important measure to prevent the spread of infections. Poor hand hygiene is often due to: the belief that the use of gloves replaces hand hygiene, lack of good example from colleagues and superiors, sinks that are difficult to access or insufficient in number, staff often too busy / not enough time, poor knowledge of guidelines and protocols. Artificial intelligence was recently integrated in hand washing devices; this can implement training on a daily basis but also is an objective method to assess the efficacy of the IPC measures adopted. The benefit–cost ratio of this approach needs to be discussed.